Applicability of the ROX index in decision-making for hospitalization in COVID-19 patients - KASAPOĞLU, UMUT SABRİ (My University, 2022)
Aim: Data on the outpatient follow-up of COVID-19 cases is still scarce. Also, the significance of the ROX index in decision-making for hospitalization in the ambulatory COVID-19 cases remains unknown. The aim of this study is to determine the general characteristics of COVID-19 patients treated as outpatients and to investigate whether the ROX index is applicable in hospitalization decisions.Material and Methods: This retrospective cohort study was conducted in confirmed adult COVID-19 cases between 15 October 2020 and 01 March 2021. A total of 5240 confirmed COVID-19 patients were included in the present study. Factors affecting hospitalization were investigated.Results: The study population was divided into two groups as those who require hospitalization (n=672) and those who did not (n=4568). The number of male patients and the mean age of the patients were significantly higher in hospitalized patients group (p=0.046, p<0.001). ROX index that was calculated at the home visit on the third day of disease was found significantly lower in the group of hospitalized patients (p<0.001). There was a significant correlation between ROX index and inflammatory biomarkers in the present study (p<0.001). The ROX index was found the most accurate parameter for decision-making for hospitalization in ambulatory COVID-19 patients (AUC=0.794 CI=0.773-0.814, p<0.001).Discussion: The ROX index can be a useful and objective clinical tool for decision making for hospitalization in the ambulatory COVID-19 cases.
Keywords: TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); COVID-19; Ambulatory; Hospitalization; Predictors; ROX Index; COMMUNITY-ACQUIRED PNEUMONIA; OUTPATIENT MANAGEMENT; VALIDATION; SEVERITY